2003
DOI: 10.1017/s0266467403003158
|View full text |Cite
|
Sign up to set email alerts
|

A baseline study of the diversity and community ecology of crab and molluscan macrofauna in the Sematan mangrove forest, Sarawak, Malaysia

Abstract: Baseline ecological studies of pristine mangroves are important for monitoring, management and conservation of mangrove ecosystems. Diversity, density, biomass and community structure of crab and molluscan macrofauna were studied in a near-pristine mangrove forest in Sematan, Sarawak. In each of the nine 100-m2 plots, six 15-min catching periods were used to collect crabs and three 1-m2 quadrats were sampled for molluscan epifauna. Environmental variables and vegetation were also recorded in each 100-m2 plot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 43 publications
2
79
0
11
Order By: Relevance
“…Gastropods in the Caribbean and elsewhere have been pointed as key detritivores and sediment grazers, even outweighing the role of crabs [80][81][82]. Available assessments on the impacts of mangrove deforestation on benthos report that vegetation provides support and physical habitat that may reduce predation and desiccation (Asia: [83,84]; Africa: [85,86]; Australia: [87]). For instance, clearing pneumatophores in small-scale deforestations for building walkways and trails was correlated with a decline in density and species richness in the entire community, particularly on gastropods [87].…”
Section: Impacts Of Selective Logging and Mangrove Reclamation On Benmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastropods in the Caribbean and elsewhere have been pointed as key detritivores and sediment grazers, even outweighing the role of crabs [80][81][82]. Available assessments on the impacts of mangrove deforestation on benthos report that vegetation provides support and physical habitat that may reduce predation and desiccation (Asia: [83,84]; Africa: [85,86]; Australia: [87]). For instance, clearing pneumatophores in small-scale deforestations for building walkways and trails was correlated with a decline in density and species richness in the entire community, particularly on gastropods [87].…”
Section: Impacts Of Selective Logging and Mangrove Reclamation On Benmentioning
confidence: 99%
“…For instance, clearing pneumatophores in small-scale deforestations for building walkways and trails was correlated with a decline in density and species richness in the entire community, particularly on gastropods [87]. In addition, community and population metrics, otherwise uncorrelated with physicochemical variables under natural conditions [84], became significantly explained by temperature and pH in deforested mangroves [86].…”
Section: Impacts Of Selective Logging and Mangrove Reclamation On Benmentioning
confidence: 99%
“…Several studies have shown a correlation between changes in the diversity and abundance of macrobenthos and the obvious variability of the environment such as the variability of habits (plants, sediment, ...) or sediment characteristics (mud, sand) [34,37,38]. Overall molluscan species recorded were mostly epifaunal, and were divided into four occupied habitats (deadwood, plant root, plant stem and substratum).…”
Section: Table1 Composition Of Collected Molluscs and Habitats Frdmentioning
confidence: 97%
“…In each station, 500 m line transect was established across the zone according to the vegetation spread. To assess the abundance and density of the crab populations, crab individuals were sampled in randomly selected 4×4 m plots along the transect, using three techniques (visual count [23], excavation [33] and crab harvest [34]) depending on species found. Harvested crabs were sedated in cold water for a few minutes, washed and stored into 70% alcohol or in a field freezer for later processing.…”
Section: Crabs Surveymentioning
confidence: 99%
“…The consequences of deforestation on mangrove fauna have not yet been documented in West Africa. The significant role of crabs as a engineer species starts to be recognized, but their ecological answers with respect to human pressures are poorly known compared to other aspects of their life such as diversity, distribution, sex ratio, ecological roles, feeding ecology, plant periodical migrations, physiological adaptations, domestic wastewater effects,… [22,23,24,25,26,27,28,29,30]. So, the aim of this study is to determine the impact of human pressures on mangrove crab biodiversity in Cameroon.…”
Section: Introductionmentioning
confidence: 99%